FEATURES THE STORAGE OF ROOT FRUITS OF SOME VEGETABLE CROPS - Деребон, І.Ю.; Руденко, Ю.Ф. (SWorldJournal, 2023)
In modern conditions, the problem of storage of plant products is of great importance. The article establishes the need to identify the impact of different storage methods on the marketability and natural mass loss of root crops of table carrots and parsn